Study on the Possibility of using Leather Fibers to Make Epoxy Composite - Bui, Van Huan; Doan, Anh Vu; Nguyen, Pham Duy Linh; Ngo, Thi Kim Thoa (Old Journal, 2019)
Vietnames footwear and leather goods industries generate large amounts of chrome tanned leather wastes and their treatment is difficult. In this study, the dry leather waste was grounded in a hammer miller, to get short leather fibers with a diameter of 0.08 ÷ 0.3 mm, length 5 ÷ 15 mm. Fibers are mixed with epoxy resin (with additives) and pressed into composite materials (with different ration of epoxy resin/leather fibers) by different press technology parameters. Composite samples were tested for breaking strength, bending strength and impact strength. The morphology of the composite material was observed by field effect electromagnetic microscope (FE-SEM). Composite materials have good properties with a leather fibers ratio of 40%. The suitable press technology parameters for the composite are pressure of 5 atm, pressing temperature of 60 oC and pressing time of 2h.